2015
DOI: 10.4049/jimmunol.1402742
|View full text |Cite
|
Sign up to set email alerts
|

Ndfip1 Regulates Itch Ligase Activity and Airway Inflammation via UbcH7

Abstract: The ubiquitin-ligating enzyme (E3) Itch plays a crucial role in the regulation of inflammation, and Itch deficiency leads to severe airway inflammation. However, the molecular mechanisms by which Itch function is regulated remain elusive. In this study, we found that nontypeable Haemophilus influenzae induces the association of Itch with Ndfip1. Both Itch−/− and Ndfip1−/− mice exhibited severe airway inflammation in response to nontypeable Haemophilus influenza, which was associated with elevated expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This study focused predominantly on Ndfip1, an activator of Itch catalytic activity24284849. It has been shown that the loss of Ndfip1 globally, or following conditional deletion in T cells, causes spontaneous autoinflammatory disease that is associated with high numbers of activated CD4 T cells, increased numbers of Th1, Th2, and Th17 cells, and premature death24262729.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused predominantly on Ndfip1, an activator of Itch catalytic activity24284849. It has been shown that the loss of Ndfip1 globally, or following conditional deletion in T cells, causes spontaneous autoinflammatory disease that is associated with high numbers of activated CD4 T cells, increased numbers of Th1, Th2, and Th17 cells, and premature death24262729.…”
Section: Discussionmentioning
confidence: 99%
“…This function of Itch appears to have in vivo relevance. Itch‐deficient mice showed increased transcriptional levels of IL‐6, TNFα, and IL‐1β in the lungs after stimulation with inactive Haemophilus Influenzae ( H. flu ) and this phenomenon was attributed to increased Tak1 activity in the absence of Itch 70 …”
Section: Itch In Innate Cell Functionmentioning
confidence: 99%
“…In addition to TNFα-induced NFκB activation, Itch inhibited NFκB responses to pattern recognition receptor ligands. Itch-dependent degradation of Rip2 or Tak1 could limit NFκB activation after BMDM exposure to Haemophilus influenza and the microbial ligand muramyl dipeptide (MDP), respectively [16,108]. Although loss of Itch in innate cells is insufficient to initiate spontaneous autoimmunity, these studies suggest that Itch helps to dampen inflammatory responses that likely drive tissue destruction and exacerbate disease after the onset of autoimmunity.…”
Section: Itch Regulates Immune Cell Function To Prevent Autoimmune DImentioning
confidence: 99%
“…Mechanistically, PY motifs within Ndfip1 interacted with Itch WW domains to relieve intramolecular autoinhibition, allowing the catalytic HECT domain to transfer ubiquitin to JunB [13,119]. Ndfip1 also was required for Itch-dependent degradation of RORγt to prevent Th17 differentiation [103] and Ndfip1 in macrophages was shown to activate Itch-dependent degradation of Tak1 to dampen NFκB signaling [108]. Recently, the Ndfip1 homolog, Ndfip2, has also been found to activate Itch.…”
Section: Molecular Regulation Of Itch Enzymatic Activitymentioning
confidence: 99%